Marcelino Chiarello: reflexões de uma trajetória de vida e significados de uma morte trágica - Capitanio, Cesar (2018)
The objective of the research was to analyze the trajectory of Marcelino Chiarello who was a teacher and councilor, in Chapecó-SC, and community and Union of Workers in Education leadership of The State of Santa Catarina (Sinte). He was found hanged at his house on November 28, 2011.The incient caused social commotion, since it was considered homicide inicially, according to the report of the lawyer who worked for Medical-Legal Institute (MLI), and by Civil Police investigations. Afterwards, police investigations were conducted for a suicide thesis, through the report of Medical-Legal Institute (MLI). After the first report, two others were presented, one being a certificate of suicide, prepared by Federal Police staff, and a second one that reported homicide thesis, prepared by the group of Legal Medicine at USP. The political formation of Marcelino was rooted in a relationship with the regional social movements, and it had a strong influence on the figure of Bishop Dom José Gomes, and on social doctrine of Catholic Church. Aspects presented to Chiarello Case start from this correlation between the process of territorial building of the west of Santa Catarina and of Chapecó in specific. There are political, cultural, economic and social elements whose accumulate, influence, denote clashes by position and power. In this respect, local political history has features of past that are based on bossism/coronelist model, with cases of political violence (e.g., lynching of 1950). Marcelino death can feature, depending on the angle of observation, or the version to the case, similarities to the political tradition based on bossism/coronelist, since when councilor, Marcelino denounced to the Public Ministry, some cases of corruption against local political actors. In this research, 3 were made interviews by the author, in addition to the analysis of interviews granted to local media. As sources of research, the analysis of the Marcelino Chiarello the CEOM, personal collection materials of Pedro Chiarello, a significant amount of journalistic materials about the case, in addition to the investigative process analysis and produced reports about the death of Marcelino and the participation in events related to the case as Seminars and the release of the Popular Judgement Case Chiarello. It was a qualitative research, whose conceptual narrative went through Walter Benjamin and the historiographical approach used was the Micro-history, passing by the Social History and Political History, making use of the methodological principle of Carlo Ginzburg known as indicting paradigm. The signification of a interrupted life by a tragic death, by the further impact, by the strong mobilizations of the Forum in Defense of Life, by justice and Democracy and other repercussions, pointed that Marcelino Chiarello´s journey constitutes historical fact, and based on Micro-History, microanalysis sought to bring elements of comprehension of Regional History which contribute to historiography.